Consistency of microvascular and autonomic abnormalities in diabetes. Issue 2 (August 1996) - Karachaliou, F H; Karavanaki, K; Greenwood, R; Morgan, H; Baum, J D
Abstract : The progression of early measures of microvascular disease and autonomic neuropathy were studied in a group of 81 children with insulin dependent diabetes mellitus over a mean interval of 4.2 years. Repeated measurements were made of blood pressure, albumin excretion, joint mobility, and pupillary dilatation in darkness. Over the years between the first and the second study, systolic and diastolic blood pressure showed positive tracking correlations (r = 0.38 and r = 0.32) with a small but significant deviation from normality; albumin/creatinine ratio was significantly increased (0.79 v 0.55); a greater number of children were identified in the second study as having limitation of mobility of the fifth metacarpophalangeal joint; and pupillary dilatation in darkness significantly decreased (61.5% v 62.9%); 62% of the children with one or more abnormal measurements in the first study were found to have measurements outside the normal ranges in the second study, indicating a consistency in observations over time. It remains to be seen with what accuracy these measurements predict adult onset clinical disease.